Diagnosis and Outcome of Oesophageal Crohn's Disease. (14th December 2019) - Vale Rodrigues, Rita; Sladek, Margaret; Katsanos, Konstantinos; van der Woude, C Janneke; Wei, Juan; Vavricka, Stephan R; Teich, Niels; Ellul, Pierre; Savarino, Edoardo; Chaparro, Maria; Beaton, David; Oliveira, Ana Maria; et al.
Abstract: Background and Aims: Crohn's disease [CD] can involve any part of the gastrointestinal tract. We aimed to characterize the clinical, endoscopic and histological features and treatment outcomes of CD patients with oesophageal involvement. Methods: We collected cases through a retrospective multicentre European Crohn's and Colitis Organisation CONFER [COllaborative Network For Exceptionally Rare case reports] project. Clinical data were recorded in a standardized case report form. Results: A total of 40 patients were reported (22 males, mean [±SD, range] age at oesophageal CD diagnosis: 25 [±13.3, 10–71] years and mean time of follow-up: 67 [±68.1, 3–240] months). Oesophageal involvement was established at CD diagnosis in 26 patients [65%] and during follow-up in 14. CD was exclusively located in the oesophagus in two patients. Thirteen patients [32.2%] were asymptomatic at oesophageal disease diagnosis. Oesophageal strictures were present in five patients and fistulizing oesophageal disease in one. Eight patients exhibited granulomas on biopsies. Proton-pump inhibitors [PPIs] were administered in 37 patients [92.5%]. Three patients underwent endoscopic dilatation for symptomatic strictures but none underwent oesophageal-related surgery. Diagnosis in pre-established CD resulted in treatment modifications in 9/14 patients. Clinical remission of oesophageal disease was seen in 33/40 patients [82.5%] after a mean time of 7 [±5.6, 1–18] months. Follow-up endoscopy was performed in 29/40 patients and 26/29 [89.7%] achieved mucosal healing. Conclusion: In this case series the endoscopic and histological characteristics of isolated oesophageal CD were similar to those reported in other sites of involvement. Treatment was primarily conservative, with PPIs administered in the majority of patients and modifications in pre-existing inflammatory bowel disease-related therapy occurring in two-thirds of them. Clinical and endoscopic remission was achieved in more than 80% of the patients.